Exploring Children's Perceptions of their Local Environment in Relation to Time Spent Outside. (19th March 2017) - Hayball, Felicity; McCrorie, Paul; Kirk, Alison; Gibson, Ann‐Marie; Ellaway, Anne
Abstract : This study aims to understand how children perceive their environment, exploring the affordances children perceive to influence their physical activity (PA) behaviour when outside. Participants included boys and girls aged 10–12 years (n = 15) living in Scotland. Children's visual and verbal representations of their perceived environment were analysed to assess environmental determinants of PA. The findings suggested that physical affordances that offer a sense of risk were important to children's play spaces. Social affordances influenced where the children went in their environment and the features they utilised as part of play behaviour; strangers were considered threatening depending on whether the activity was recognised.